Measurement of radiative Bhabha and quasi-real Compton scattering - Dova, María Teresa (1998)
We report on a study of radiative Bhabha and quasi-real Compton scattering at centre-of-mass energies between 50 GeV and 170 GeV, and 20 GeV and 140 GeV, respectively, using the L3 detector at LEP. The analysis is based on data corresponding to an integrated luminosity of 232.2 pb-1 . A total of 2856 radiative Bhabha and 4641 Compton scattering events are collected. Total and differential cross sections for both reactions are presented and found to be in good agreement with QED expectations. Our measurement of Compton scattering at the highest energies obtained so far is used to derive exclusion limits on the coupling λ for the on-shell production of an excited electron e★ decaying into a γe pair in the mass range 20 GeV < me★ < 170 GeV.